Intensive thermal exploitation from closed and open shallow geothermal systems at urban scale: unmanaged conflicts and potential synergies. (July 2022) - Perego, Rodolfo; Dalla Santa, Giorgia; Galgaro, Antonio; Pera, Sebastian
Highlights: Electrification of building thermal energy demand is more often provided by SGS Cumulative effects on urban groundwater temperature are observed A numerical model of SGS exploitation was built and calibrated against real data Model outcomes reveal the presence of mutual negative and positive interferences Technical suggestions are proposed for a more sustainable management Abstract: The use of shallow geothermal systems (SGS) as a proficient technology to provide clean thermal energy has become increasingly widespread throughout the world, especially in urban environments, with a significant increase in systems density. At European level, the current authorization schemes for new SGS rarely consider the current thermal state of the subsurface and the potential presence of neighbouring systems. The paper presents a pilot urban case study, showing high SGS deployment, analysed through a holistic city-scale 3D numerical model simulating mutual interactions between open and closed-loop systems. Results show that the high amount of installed SGS in limited space is progressively creating mutual hydraulic and thermal interferences: negative, with a reduction of SGS efficiency and sustainability or (rarely) positive, when an accidental and unmanaged synergic effect is established due to favourable exploitation patterns and SGS locations. Numerical modeling further highlighted that the restitution through the vadose zone could be a valid method to hydraulically reinstate the aquifer without significantly altering groundwater undisturbed temperature even at shallow groundwater depth. Results show that neglecting an underground holistic vision of the hydro/thermogeological processes in urban areas could result in long-term severe efficiency losses and environmental issues for SGS solutions, also given the increasing use of shallow geothermal energy in the building air conditioning sector. Graphical Abstract: Image, graphical abstract